Kajian ilmu Ashwat: Realisasi vokal pendek dan panjang dalam meminimalisir lahn jali saat membaca Al-qur’an - Al Mahbubi, Muhammad Rusydan (Maliki Interdisciplinary Journal, 2026)
This study investigates the vital role of realizing short vowels (single harakat) and long vowels (Mad/tanwin) from the perspective of ‘Ilm al-Aṣhwāt (Phonetics) in minimizing critical errors (La ḥ n Jalī) when reciting the Qur’an. 30Accurate and fluent recitation is a crucial aspect of worship, requiring precise pronunciation to maintain the integrity of the verses' meaning. 31La ḥ n Jalī is defined as a clear and obvious pronunciation error that directly changes or affects the meaning of the recitation. 32The main problem is the lack of understanding among reciters, especially beginners, regarding the application and differentiation of duration between short vowels (one harakat) and long vowels (two or more harakat), frequently leading to La ḥ n Jalī. 33In Arabic, this difference in vowel duration is essential for distinguishing word meanings. 34Video analysis case studies illustrate how errors in substituting, shortening, or lengthening vowels can alter the verse's meaning (e.g., warsuulahu (ورسولَه) instead of the correct warsuuluhu (ورسولُه), or shortening the long vowel in yaquuluu qad (يقولُوا قد)). 35Employing a qualitative approach with descriptive analysis of Qur'an recitation videos, this research aims to effectively optimize the realization of short and long vowels to reduce La ḥ n Jalī. 36Findings indicate that vowel duration is critically important yet still receives insufficient attention. 37Therefore, it is recommended that educational institutions strengthen their ‘Ilm al-Aṣhwāt and 38Tajwid curricula to focus on vowel duration. 39Additionally, reciters should utilize digital media critically, and instructors should implement a two-way training method (audiovisual and direct feedback) to enhance the reciters' auditory sensitivity.